Kahoot! as innovation gamification for examination - Efrilla Niza; Aura Salsabilah Ardian (Curricula: Journal of Curriculum Development, 2022)
Kahoot! is a learning innovation with a gamification method in the form of a platform. This study used a literature review method based on various research results that discuss the implementation of learning using web-based media. The data analysis consists of reading the literature review, summarizing, analyzing, and synthesizing it. The results of this study indicate that in carrying out the learning process, educators need to follow technological developments. By using Kahoot! As a medium for conducting exams or tests, students will get a new and fun experience while doing their exams. This is supported by the website's visual appearance, which uses funny and exciting animations. In addition, in its use, There is no charge, and the application is relatively easy to use. However, the downside of using Kahoot! as a learning media, both educators and students need a good internet network and adequate devices. Kahoot! can be used as an alternative media in learning because of its advantages, but it should also be noted that in its use, Kahoot! Requires a good internet connection and adequate devices.